Ecologia da comunidade de metazoários parasitos do sairú Cyphocharax nagelii do Rio do Peixe - Vieiral, Diego Henrique Mirandola Dias [UNESP]; Caramello, Luhan Eduardo [UNESP]; Abadallah, Vanessa Doro; da Silva, Reinaldo José [UNESP]; de Azevedo, Rodney Kozlowiski (My University, 2013)
A total of 57 sairus (Cyphocharax nagelii) from the Peixe River, state of São Paulo, southeastern Brazil, were examined between April 2011 and February 2012. Eleven species of metazoan parasites were collected and identified: Palombitrema triangulum, Curvianchoratus hexacleidus, Curvianchoratus singularis, Sphincterodiplostomum musculosum, Contracaecum sp., Cacatuocotyle paranaensis, Cosmoxynemoides aguirrei, Amplexibranchius bryconis, Brasergasilus sp., Ergasilus sp. and Clinostomum sp. The monogenean P. triangulum was the most prevalent species (61.40%) with the highest mean intensity (4.88). The monogeneans C. hexacleidus and C. singularis, the digenean S. musculosum and the nematode Contracaecum sp. also showed high prevalence. Only S. musculosum presented significant correlation between the total body weight of the host and its abundance. The parasitic infracommunities had a mean Brillouin diversity (HB) of 1.165 ± 0.987 and the maximum diversity was 1.671. The sex and length of the hosts did not influence the abundance of any parasite species. The community of metazoans in C. nagelii from the Peixe River was characterized by high richness and low uniformity.
Community ecology of metazoan parasites of the sairú Cyphocharax nagelii from the Peixe River
Keywords: Brazil; Curimatidae; Fish; Parasites; Peixe River